(untitled) (Journal of Health Sciences, 2023)
Introduction: Surgical treatment of inguinal hernia is one of the most common procedures in surgery. Various techniques can be used to repair inguinal hernias, but the two most commonly used are the Shouldice surgical technique, modified by the Berliner Darn and Lichtenstein techniques, as a non-extension technique. However, despite the long tradition of surgical hernia treatment, there is still no consensus on the best or most appropriate surgical technique for elective inguinal hernia repair. Therefore, it remains a challenge for surgeons to choose the appropriate hernia repair method on a case-by-case basis that results in low complications and faster recovery. The aim of this study is to compare the efficiency of the Shouldice surgical technique modified by the Berliner Darn and Lichtenstein techniques in the treatment of hernias with respect to certain post-operative parameters. Methods: A prospective and cohort study was conducted at the Clinical Hospital in Tetovo. The study included 100 patients diagnosed with inguinal hernia and treated in hospital. The monitored patients were divided into two groups according to the technique used: 50 patients treated with Shouldice technique modified by Berliner Darn and 50 patients treated with Lichtenstein technique. In addition, we based the selection of the groups mainly on the reproductive age of the patients. Only male patients were treated in both groups, as there were very few female cases during the study period. Results: Patients operated on with the Lichtenstein technique were more mobile postoperatively, post-operative pain was less severe and return to daily and occupational activities and length of hospital stay were significantly shorter than with the Shouldice technique. Conclusion: The Lichtenstein tension-free surgical technique is more efficient and adequate than the modified Shouldice technique according to Berliner Darn in terms of post-operative pain intensity, length of hospital stay, return to daily activities, and return to work.